QUE DIOS Y MI FAMILIA ME LO DEMANDEN. POSIBLES FUENTES DE LA EJEMPLARIDAD FEMENINA EN IV MACABEOS (Stylos, 2019)
The textual frame of the IV Book of the Maccabees has stirred profound debates due to the difficulties that exist in determining the quantity and quality of its influences. Many traditions from Hellenistic and even Roman fields can be read between its lines to characterize the main characters both morally and ethically. With this scope, the martyrs –which are the link between this work with its source, the canonical II Maccabees– gather inside themselves a series of preexistent textual topics linked to atonement and sacrifice. In this work we will try to prove, consequently, how the character of the mother develops itself as from two literary pillars both equally important: on one hand, the euripidean Alcestis; on the other hand, the Orion’s daughters, briefly mentioned by Ovid in Met. 13.692-699. The union of the two sources will result in the convergence of the political-familiar aspect and the religious one in the mother’s character at the time of her death.
Keywords: Atonement – Biblical exegesis – intertextuality – IV Maccabees